2020
DOI: 10.3390/rs12071184
|View full text |Cite
|
Sign up to set email alerts
|

An Optimal Population Modeling Approach Using Geographically Weighted Regression Based on High-Resolution Remote Sensing Data: A Case Study in Dhaka City, Bangladesh

Abstract: Traditional choropleth maps, created on the basis of administrative units, often fail to accurately represent population distribution due to the high spatial heterogeneity and the temporal dynamics of the population within the units. Furthermore, updating the data of spatial population statistics is time-consuming and costly, which underlies the relative lack of high-resolution and high-quality population data for implementing or validating population modeling work, in particular in low-and middle-income count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…From TAE statistics, we found that GWR models perform better than OLS models. This confirms the findings in the literature [22,[92][93][94][95], as GWR considers spatial non-stationarity from the reconstructed residential land cover/use map. The gridded population distribution maps obtained using the GWR approach can be used to analyse spatio-temporal patterns of population density in the Bursa region and can be used as an input in future studies focusing on exploring population dynamics in Turkey.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…From TAE statistics, we found that GWR models perform better than OLS models. This confirms the findings in the literature [22,[92][93][94][95], as GWR considers spatial non-stationarity from the reconstructed residential land cover/use map. The gridded population distribution maps obtained using the GWR approach can be used to analyse spatio-temporal patterns of population density in the Bursa region and can be used as an input in future studies focusing on exploring population dynamics in Turkey.…”
Section: Discussionsupporting
confidence: 90%
“…Dasymetric modelling methods use ancillary data along with geographic information systems (GIS) and remote-sensed data to refine the geographical representation of the census variable reported as coarse spatial aggregations. Land cover/use, night lights, geophysical factors, urban/rural areas, building data and roads have been used as ancillary data to disaggregate population to fine-scale maps [21,22]. Although land cover/use data have been recognised as the best option to reflect population density [23], the data that are required from remote sensing images do not exist to model the distribution of historical population.…”
Section: Introductionmentioning
confidence: 99%
“…The WorldView-2 satellite was launched into space on October 6, 2009, and has accumulated sufficient data so far. Its primary advantages include flexible operation, a large capacity, fast return visits, accurate shooting, high-definition image capturing, and the availability of multiple color bands [46]. These advantages provide us with sufficient and reliable high-resolution remote sensing data sources.…”
Section: A Study Area and Remote Sensing Datamentioning
confidence: 99%
“…Therefore, the accurate delineation of urban–rural boundaries helps with distinguishing urban from rural areas for the formulation of reasonable urban and rural development planning methods, to then further alleviate the environmental problems in the process of urban and rural development, and achieve the healthy development of urban and rural areas [ 15 ]. However, due to the significant differences between urban and rural areas in terms of the economic development level and infrastructure, urban–rural boundaries were previously delineated based on economic, population, and other statistical data [ 16 ]. In previous studies, the statistical data of the whole urban and rural areas were generally divided into different levels, with the higher level being the urban area and the lower level being the rural area, then the urban and rural areas were delineated.…”
Section: Introductionmentioning
confidence: 99%
“…As data that can reflect the differences in urban spatial surface information, urban remote sensing has gradually replaced the use of traditional statistical data, such as administrative indicators, economic, and population statistical data, due to their advantages, including a larger spatial scale, wider collection range, and more connected time scale [ 16 , 18 , 19 ]. As one of the most widely used remote sensing data, NTL data mainly reflect the difference between urban and rural development levels by representing the light brightness of urban buildings and infrastructure at night [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%